2015
DOI: 10.1016/j.sbspro.2014.12.617
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Relationship between Attachment Styles and Obsessive Love Style

Abstract: The aim of this study was investigating the relationship between the attachment styles and obsessive love style of university students. The samples included 306 graduate students University of Nyshaboor-Iran that were selected with proportional random assignment procedure. The data were collected by using Adult Attachment Style (AAQ) and Love Attitude Style (LAS) Questionnaires. By employing SPSS software, the data were analyzed by using Pearson correlation coefficient and Multiple Variable Regression procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
10
0
3
Order By: Relevance
“…Thompson (1996) have found out that selfless love is highly related to compulsive and obsessive personal traits. In another research (Kanemasa et al, 2004;Honari and Saremi 2015) , which investigated the link between different types of love and emotional experiences , it is found that selfless love is related to such negative traits as anxiety, jealousy, and incompatibility. Possessive love style is also found to be linked to negative psychological factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thompson (1996) have found out that selfless love is highly related to compulsive and obsessive personal traits. In another research (Kanemasa et al, 2004;Honari and Saremi 2015) , which investigated the link between different types of love and emotional experiences , it is found that selfless love is related to such negative traits as anxiety, jealousy, and incompatibility. Possessive love style is also found to be linked to negative psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…As it is stated in the relevant article, it is revealed in the research that love types and satisfaction level in a relationship are affected by both positive and negative factors. (Zeigler-Hill et al 2015;Honari and Saremi, 2015;Zeigler-Hill and Abraham, 2006). Based on the claim by Vallerad et al (2006) that there is a link between positive and negative emotions and harmonious and obsessive passions, the aim of this research is to investigate the role of their passion for sports in determining attitude to love and relation satisfaction with the sample of sportsmen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existen estudios que muestran la relación entre los estilos de amor, estilo de apego y relaciones de 'mal trato', identifican el amor obsesivo (Manía) como el desencadenante o causante de las relaciones violentas (Ahmadi et al, 2013;Honari y Saremi, 2015), pero escasean los que relacionen el amor romántico y las creencias a él adscritas.…”
Section: Figura 1 Estilos De Amor Previos Y Posteriores a La Formaciunclassified
“…Other studies emphasized that anxious styles are characterized by low satisfaction in their relationship and low trust in their partners, but their relationships include high, obsessive commitment (Stephan & Bachman, 1999). Honari and Saremi (2015) showed that ambivalent anxious attachment is related to mania love type.…”
mentioning
confidence: 99%